High Temperature Dry Sliding Reciprocating Wear Behavior of Centrifugally Cast A356-Mg2Si In-Situ Functionally Graded Composites - Ram S.C.; Chattopadhyay K.; Bhushan A. (My University, 2025)
In this study, the Al-Mg2Si FG-composites were developed by in-situ centrifugal casting route with varied Mg contents (2.5, 5.0, 7.5, and 10.0 wt.% Mg). Cast FG-composites subjected to T6 heat treatment processes to achieve the high specific wear resistance and mechanical properties. High temperature linear reciprocating wear and friction properties of in-situ centrifugally cast A356-Mg2Si FG-composites has been studied. The wear resistance properties of Al-Mg2Si FG-composites were characterized by difference of initial and final weight measurement after sliding wear test. As a result, the mass loss decreases steadily as the %Mg increases from 2.5% to 7.5% and slightly increases with 10% Mg. The FG-composites containing 7.5%Mg exhibits the remarkable combination of wear resistance characteristics and coefficient of friction. Microstructural features and phases distributions were analyzed with the help of Optical and SEM microscopy. The surface topography of wear test samples were carried out using the Scanning Electron Microscopy (SEM) followed by Energy-dispersive X-ray spectroscopy (EDX) analysis. Graphical Abstract: [Figure not available: see fulltext.]. © 2022, The Author(s), under exclusive licence to Springer Nature B.V.